Missugust omakultuuri hoiame tantsupidudel? - Sille Kapper (Mäetagused, 2016)
Estonian Song and Dance Celebrations take place every five years, involve thousands of participants and great audiences in venues or via the media. In Estonia the tradition of dance celebrations as well as (stage) folk dance in hobby groups dates back to the beginning of the twentieth century. In the learning processes and programmes of dance celebrations traditional folk dance is used in the format of some single elements or features only. In a situation like this it is important to ask what role dance celebrations play in preserving and passing on the knowledge and skills connected with traditional dancing in contemporary Estonia. Which concepts and realisations of a dance may be compatible with the process of dance celebrations, and which of them are left aside and why? The article is based on the author’s dance ethnography (2008–2105) in two dance worlds, which partially overlap each other: it is the traditional folk dancing on the one hand, and the (stage) folk dance as a hobby, including participation in dance celebrations, on the other. The study shows that it is ourselves who create those institutional truth regimes that promote certain ideas while overshadowing alternative knowledge, although important for the preservation and sustainable development of our national culture. The main conclusions of the study are as follows: Dance celebrations do not support the propagation of the plural and diverse nature of traditional culture (on the example of traditional dancing) because their principal output, the massive productions, are not designed for that purpose, have other strengths and also other requirements in connection with its specialty to address large crowds at rather long distances. The format of dance celebration suits well for highlighting the positive, unified, and common values of national culture, while social criticism is not an attitude readily adopted, either by participant dancers or by the audience, even if such an approach is proposed by a creative team. Although the agency of the lived body as a source of knowledge can generally be well utilised in increasing one’s self-awareness in dancing, the dance celebration processes do not enhance the personal agency of participant dancers – most choices are made by the artistic teams and group leaders while the dancers’ main task is to obey the rules. This could be seen as a point of concern because low agency, meaning here unwillingness and poor ability to make intended decisions, may easily lead to alienation from the values important for the tradition of dance celebration itself and Estonian national culture as a whole.